PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA ASSEMBLR EDU TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD SWASTA KATOLIK DISKI - Sitorus, Irmatansy Alodya; Nova Florentina Ambarwati; Ester Julinda Simarmata; Joen Parningotan Purba; Paska Sriulina Tarigan; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the Influence of the Problem Based Learning Model Assisted by Assemblr Edu Media on the Critical Thinking Ability of Grade V Students of Diski Catholic Private Elementary School for the 2025/2026 Academic Year. This study uses a quantitative approach with a pre-experimental design method through a one-group pretest-posttest design and the research sample was selected using the purposive sample technique with a sample of 27 students. The results showed that the average pretest score was 62,407 and the average posttest score was 86,620, so that there was an increase in students' critical thinking skills after applying the problem based learning model assisted by edu assembly media. The results of the paired t-test showed a calculated t-value of 7.568 with a significance value (Sig.2-tailed) of 0.000. Since the significance value is 0.000 < 0.05, Ha is accepted and H0 is rejected. In addition, when compared with the value of t of the table at the significance level of 5% and df = 26, which is 2.056 (two sides), then tcalculation is obtained of 7.568 with tof table 2.056 so that tcalculates ≥ tof the table. With this, it can be concluded that there is a significant difference between the pretest and posttest scores. The application of the problem-based learning model assisted by the edu assembly media has a positive and significant effect on students' critical thinking skills.